Evaluating crop growth between hydroponics and aquaponics with different light inputs - Heo, Jeongwook; Baek, Jeonghyun; Subah, Zarin; Ryu, Jae Hyeon (Frontiers in Horticulture, 2024)
Indoor farming technologies, such as aquaponics and hydroponics, are crucial for advancing sustainable agriculture, especially in urban areas with limited land for conventional agriculture. As studies comparing these two systems are limited, this study explored the cultivation of five leafy vegetables—white leaf beets (Beta vulgaris var. cicla), hooker chives (Allium hookeri), basil (Ocimum basilicum), lemon balm (Melissa officinalis), and spearmint (Mentha spicata)—in an indoor greenhouse facility using two different food production platforms: an aquaponic system (AS) with catfish (Silurus asotus) and a conventional hydroponic system (HS). The results showed that the plant growth in AS outperformed that in HS, while the general growth patterns in AS were significantly affected by the different light sources. In addition, the leaf yield of the herbal plants (basil and lemon balm) in AS was 60%–70% more than that in HS. The leaf growth of hooker chives in AS also showed significant improvement (200%) compared with that in HS. It appears that the nutrient sources provided by fish were remarkable, as the average concentration of NO3–N (64 mg/L) was easily achieved in AS. The proposed AS, therefore, would be a promising alternative to the production and supply of supplement organic food, ultimately contributing to promoting sustainable agriculture in a changing climate.